Pengaruh Harga, Kemasan Produk, Kualitas Produk, dan Store Atmosphere terhadap Keputusan Pembelian Konsumen yang Diintervensi oleh Variabel Kepuasan Konsumen pada Toko Virsya Jajanan Oleh -Oleh Khas Trenggalek - Nana Melia; Ali Mauludi AC (J-MAS (Jurnal Manajemen dan Sains), 2023)
The aims of this study are 1) to measure the direct and indirect effects of price, product packaging, product quality, and store atmosphere on purchasing decisions with consumer satisfaction as the intervening variable, and 2) to determine the total amount of each of the effects of price, packaging product, product quality, and store atmosphere on purchasing decisions at the Virsya Snacks Typical Souvenirs of Trenggalek. This research approach is quantitative. This type of research is causal comparative. The data analysis technique of this study is multiple linear regression. Comparative causal research is research that compares which has the stronger direct or indirect effect of each independent variable on the dependent variable and compares the total amount of influence of each independent variable. The population of this study is Virsya Shop consumers and the number is unknown. The sample used is 100 respondents. The sampling method is by filling out a questionnaire which is distributed to consumers who come to the Virsya Store. The test results in this study indicate that price has a significant positive effect on customer satisfaction, price has no effect on purchasing decisions, product packaging has no influence on consumer satisfaction, product packaging has no influence on purchasing decisions, product quality has no effect on customer satisfaction , Product quality has a positive influence on purchasing decisions, Store atmosphere has a positive influence on consumer satisfaction, Store atmosphere has a positive influence on purchasing decisions, Consumer satisfaction has a positive influence on purchasing decisions, Consumer satisfaction has a role in mediating prices on purchasing decisions, Consumer satisfaction does not provide a role in mediating product packaging on purchasing decisions, consumer satisfaction does not provide a role in mediating product quality on purchasing decisions, customer satisfaction Consumers do not play a role in mediating store atmosphere on purchasing decisions at the Virsya Snack Shop, Typical Souvenirs of Trenggalek.